Effects of E‐cigarette E‐liquid components on bronchial epithelial cells: Demonstration of dysfunctional efferocytosis. Issue 6 (22nd September 2019) - Ween, Miranda P.; Hamon, Rhys; Macowan, Matthew G.; Thredgold, Leigh; Reynolds, Paul N.; Hodge, Sandra J.
ABSTRACT: Background and objective: E‐cigarettes are often marketed and thought of as emitting harmless vapour; however, verification of their safety for non‐smokers is scarce. We have previously shown that E‐cigarettes cause decreased phagocytosis of bacteria by macrophages via reductions in surface bacterial recognition receptors. This study assessed the effect of E‐cigarette constituents, 3 E‐liquid apple flavours, nicotine, vegetable glycerine and propylene glycol, on bronchial epithelial cell viability, apoptosis and cytokine secretion and macrophage phagocytosis of apoptotic airway cells and phagocytic recognition molecules. Methods: Cell necrosis and apoptosis were measured by Sytox Green stain and Annexin V. Efferocytosis was measured by internalization of pHrodo Green labelled apoptotic airway cells by macrophages. Expression of macrophage cell surface apoptotic cell receptors was measured by flow cytometry. Cytokine release by E‐cigarette‐exposed airway cells was measured by cytokine bead array. Results: E‐cigarette vapour increased primary bronchial epithelial necrosis and apoptosis. E‐cigarette vapour reduced efferocytosis (lowest flavour 12.1%) versus control (20.2%, P = 0.032). The efferocytosis receptor CD44 was reduced by one flavour (MFI 1863 vs 2332 control, P = 0.016) and all components reduced expression of CD36, including the glycol bases (MFI 1067–12 274 vs 1415 control). Reduced secretion of TNF‐α, IL‐6, IP‐10, MIP‐1α and MIP‐1β was observed for all flavour variants. Conclusion: E‐cigarettes can cause bronchial epithelial apoptosis and macrophage efferocytosis dysfunction via reduced expression of apoptotic cell recognition receptors. These data further show that E‐cigarettes should not be considered harmless to non‐smokers and their effects may go far beyond cytotoxicity to cells. Abstract : E‐cigarettes are increasing in popularity, especially amongst non‐smokers. We assess not only the toxicity of E‐cigarettes on healthy airway epithelial cells and effect on secreted cytokines, but also, for the first time, the effect on efferocytosis of apoptotic airway cells by macrophages. See related Editorial See cover image